2001
DOI: 10.1590/s0100-83582001000100005
|View full text |Cite
|
Sign up to set email alerts
|

Épocas de consórcio de alho com cenoura em três sistemas de manejo de plantas daninhas em Jaboticabal-SP

Abstract: Com o objetivo de estudar o sistema de cultivo consorciado das culturas de alho (Allium sativum) e cenoura (Daucus carota) no município de Jaboticabal-SP, testaram-se quatro épocas de semeadura da cenoura (0, 15, 30 e 45 dias após o plantio do alho) combinadas com três manejos de plantas daninhas (herbicida, capinas freqüentes e sem controle). Determinaram-se os efeitos deste consórcio no controle de plantas daninhas, no uso eficiente da terra (UET) e na rentabilidade agrícola. Utilizou-se o delineamento exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
(7 reference statements)
0
4
0
2
Order By: Relevance
“…The results from the work developed under field conditions, by Ferrari Neto et al (2011), of burning down the straw residues of Cajanus cajan and millet (Pennisetum glaucum) species in both single and intercropping cultivations suggest that there is no hindrance to castor bean development. Novo et al (2007) found that the addition of sugar cane straw to the soil surface did not change the emergence of castor beans, but interfered with the initial development of specific castor bean genotypes (IAC Guarani, Iris and IAC-2028). The authors also verified that vinasse application (150 m 3 ha -1 ) reduced castor bean emergence; however, there was no damage subsequent to seedling development that occurred from the presence of this residue.…”
Section: Control Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…The results from the work developed under field conditions, by Ferrari Neto et al (2011), of burning down the straw residues of Cajanus cajan and millet (Pennisetum glaucum) species in both single and intercropping cultivations suggest that there is no hindrance to castor bean development. Novo et al (2007) found that the addition of sugar cane straw to the soil surface did not change the emergence of castor beans, but interfered with the initial development of specific castor bean genotypes (IAC Guarani, Iris and IAC-2028). The authors also verified that vinasse application (150 m 3 ha -1 ) reduced castor bean emergence; however, there was no damage subsequent to seedling development that occurred from the presence of this residue.…”
Section: Control Methodsmentioning
confidence: 93%
“…In general, for many agricultural crops, integrated weed management has contributed to more effective and sustainable weed control (ACCIARESI et al, 2003;MACHADO et al, 2006;GALON et al, 2007;RONCHI et al, 2008;PACHECO et al, 2009;FERREIRA et al, 2010;BIANCHI, 2010). This integration uses several control techniques to minimize weed interference in crops, keeping weed populations at levels below those that cause economic damage, while also mitigating negative effects on the environment (RONCHI et al, 2010).…”
Section: Integrated Weed Management In Castor Beanmentioning
confidence: 99%
See 1 more Smart Citation
“…Outra estratégia interessante no sentido de antecipar a cobertura do solo, restringindo espaço e outros fatores essenciais ao crescimento das plantas daninhas, especialmente a luminosidade, é a consorciação de culturas, que segundo Mueller et al(2001);Mueller et al, (2004); pode ser uma alternativa econômica e ecologicamente viável no manejo de plantas daninhas.…”
Section: Introductionunclassified
“…Como exemplo, podem-se citar trabalhos cujos estudos envolveram culturas de tomate com milho (Adelana, 1984); algodão e alho (Parbo Jr. et al, 1989); alho e cenoura (Mueller et al, 2001); e alho e beterraba (Mueller et al, 1998). Todos esses trabalhos apresentaram rentabilidade econômica favorável ao sistema de cultivo consorciado.…”
unclassified